Biostable L‑DNAzyme for Sensing of Metal Ions in Biological Systems - Cui, Liang; Peng, Ruizi; Fu, Ting; Zhang, Xiaobing; Wu, Cuichen; Chen, Huapei; Liang, Hao; Yang, Chaoyong James; Tan, Weihong (Analytical chemistry (Washington), 2016)
DNAzymes, an important type of metal ion-dependent functional nucleic acid, are widely applied in bioanalysis and biomedicine. However, the use of DNAzymes in practical applications has been impeded by the intrinsic drawbacks of natural nucleic acids, such as interferences from nuclease digestion and protein binding, as well as undesired intermolecular interactions with other nucleic acids. On the basis of reciprocal chiral substrate specificity, the enantiomer of D-DNAzyme, L-DNAzyme, could initiate catalytic cleavage activity with the same achiral metal ion as a cofactor. Meanwhile, by using the advantage of nonbiological L-DNAzyme, which is not subject to the interferences of biological matrixes, as recognition units, a facile and stable L-DNAzyme sensor was proposed for sensing metal ions in complex biological samples and live cells.